HOST PREFERENCE AND POPULATION DENSITY OF THE SMALL CABBAGE WHITE BUTTERFLY Pieris rapae (L.) (Lepidoptera: Pieridae) (Mesopotamia Journal of Agriculture)
The study was carried out at the Grda Rasha field station of Agricultural researches which belongs to the college of Agriculture / Salahaddin University - Erbil, Kurdistan Region of Iraq, to investigate the host preference of small cabbage white butterfly, Pieris rapae (Linnaeus, 1758) on some crops of the family Brassicaceae and to estimate population density of the immature stages on two cultivars of Cabbage and Cauliflower crops. The results pointed to that Cauliflower variety were the preferred host for attracting of the adult females for eggs laying followed by the Cabbage, the Turnip and the Radish crops revealed low sensitivity to this insect during the research period. The highest mean of the egg and larval population density recorded in the second week of November were 2.69 egg/plant, 3.38 larva/plant respectively, and the higher mean of 1.83 pupa/plant was recorded in the second week of January, and the insect have nine generations in the year.